Joint pricing, inventory, and preservation decisions for deteriorating items with stochastic demand and promotional efforts - Hardik N. Soni; Ashaba D. Chauhan (Journal of Industrial Engineering International, 2018)
This study models a joint pricing, inventory, and preservation decision-making problem for deteriorating items subject to stochastic demand and promotional effort. The generalized price-dependent stochastic demand, time proportional deterioration, and partial backlogging rates are used to model the inventory system. The objective is to find the optimal pricing, replenishment, and preservation technology investment strategies while maximizing the total profit per unit time. Based on the partial backlogging and lost sale cases, we first deduce the criterion for optimal replenishment schedules for any given price and technology investment cost. Second, we show that, respectively, total profit per time unit is concave function of price and preservation technology cost. At the end, some numerical examples and the results of a sensitivity analysis are used to illustrate the features of the proposed model.
Keywords: 650; Pricing; Inventory; Preservation technology investment; Promotion